Aktivitas Antipiretik Pada Senyawa Berkhasiat Dari Berbagai Tanaman Obat - Khafifah Nanda Permata Sari (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2023)
Indonesia is one of the largest countries for medicinal plants in the world, various types of plants in Indonesia are used in generations. parts that are often used are roots, wood, leaves, fruit and seeds in fever medicine plants, there is an increase in body temperature that is directly related to the lithogenic sitokin level used to overcome various stimuli. antipyretic drugs are drugs used to overcome fever. The purpose of this article is made to find out which medicinal plants can be used as fever reducers. The method used is literature searches from national and international journals. From the results obtained by papaya plants (Carica papaya L.), turmeric (Curcuma longa Linn.), pepper (Piper nigrum L.), pare (Momocardica charantia), and starfruit (Averrhoa blimbi L.) has an active compound that can play an antipyretic drug